THE IMPACT OF MATERIAL AND TECHNICAL CONDIONS AND METHODS OF ORGANISATION ON THE ANTHROPOMETRIC STATUS OF ADOLESCENTS - Milana Katanić,; Miroslav Smajić,; Višnja Đorđić,; Alen Kapidžić,; Branka Protić-Gava,; Ksenija Bošković, (Sport Scientific And Practical Aspects, 2025)
Physical education class presents an organised form of activities for children, in the educational system, as well as sport sections, school competitions, sport days. The fact is that the real situation is not often suitable for conducting the classes with specific teaching units, but schools generally have unsuitable space for physical education classes or do not have it at all. Under such technical and material conditions or without them at all, expertise of a teacher comes to the fore. The skillfulness reflects in necessity of adjusting that is modifying the curriculum. The aim of the research is to determine differences between examinees in terms of anthropometry, depending on material and technical conditions and methods of class organization, i.e. curriculum implementation. The participants in the study were 142 adolescent, 17 years of age (± 6 months). In order to assess anthropometric features, anthropometric measurements were used. Data processing was done by applying multivariate analysis of covariance (MANCOVA); significance of difference was determined by analysis of variance (ANOVA), while differences among examinees of the experimental and the control group were determined by discriminant analysis. After the experimental treatment, it was determined that there was not statistically significant difference between the experimental and the control group within the anthropometric measures system.